Comparison of the effect and treatment sequence between a 2-week parallel repetitive transcranial magnetic stimulation and rehabilitation and a 2-week rehabilitation-only intervention during a 4-week hospitalization for upper limb paralysis after stroke: An open-label, crossover observational study. (20th January 2022) - Yamada, Naoki; Kashiwabara, Kazumi; Takekawa, Toru; Hama, Midori; Niimi, Masachika; Hara, Takatoshi; Furumizo, Satoshi; Tsuboi, Marika
Background: NEURO ® is a 2-week program that combines low-frequency repetitive transcranial magnetic stimulation (rTMS) and intensive occupational therapy (OT) to treat patients with chronic hemiparesis following stroke. The degree to which each element contributes to the improvement of upper limb function remains unclear. It has been suggested that low-frequency rTMS applied to a healthy cerebrum activates neural activity in the contralateral hemispheric area surrounding the lesion. Intensive OT performed in parallel to rTMS promotes the functional remodeling of the cerebrum to help with rehabilitation. Objectives: However, this has not been demonstrated using NEURO ® . Therefore, we aimed to compare the effects of the NEURO ® and OT-only protocols in patients with hemiparesis following stroke. Methods: Thirty-seven patients with upper limb paralysis following stroke were recruited and hospitalized for treatments and randomly divided into two groups. Group A consisted of 16 patients who underwent NEURO ® for the first 2 weeks, and Group B consisted of 21 patients who underwent OT-only for the first 2 weeks. After 2 weeks of hospitalization, the treatments of Groups A and B were reversed for the subsequent 2 weeks of treatment. Improvement in upper limb motor function in Groups A and B at 2 and 4 weeks after the start of treatment was evaluated using the Fugl-Meyer Motor Assessment (FMA) and the Wolf Motor Function Test (WMFT). Results: Group A, who underwent NEURO ® first during their initial 2-week hospitalization, showed significantly greater improvement than that in Group B, who underwent OT-only first ( P = .041 for FMA and P < .01 for WMFT). At 4 weeks following the reversal of treatments, Group A who underwent NEURO ® and then OT-only showed significantly greater improvement than that in Group B, who underwent OT-only followed by NEURO ® ( P = .011 for FMA and P = .001 for WMFT). Conclusion: Our findings indicate that rTMS facilitates neuromodulation when combined with OT, which leads to more effective rehabilitation than with OT alone (Trial registration: JMACCT (http://www.jmacct.med.or.jp/ ); trial ID JMA-IIA00215).